MOTION GRAPHIC DESIGN OF AUTOMATED UVC TROLLEY INTRODUCTION AT THE LIPI TECHNOLOGY INFORMATION CENTER BANDUNG - Arya, Arya Sindhora; Saputra, Deni; Tisnawati, Rini (INFOKOM (Informatika & Komputer), 2022)
This study aims to introduce the Automated UVC Trolley (AUT) as a disinfectant tool that can be developed well. This study examines the media developed by UPT BPI LIPI to introduce the tool.Which in the use of the promotion field by implementing Multimedia, especially Motion Graphics, has a very good impact on the community, one of which is the introduction of the Company Profile. In this study, researchers used 3 software from Adobe Corporation. namely Adobe Premiere Pro, Adobe Illustrator and Adobe After Effects. Therefore, researchers apply Motion Graphic as a promotional media in the form of products or services because it is considered the most efficient in the field of information and technology.